2011
DOI: 10.1007/s10854-011-0445-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen flow rate on photocatalytic TiO2 films deposited by rf magnetron sputtering

Abstract: Titanium dioxide (TiO 2 ) thin films having anatase (1 0 1) crystal structure were prepared on nonalkali glass substrates by rf (13.56 MHz) magnetron sputtering using a TiO 2 ceramic target under various oxygen partial pressures. At a fixed substrate temperature of 400°C and total gas pressure of 1 Pa after 3 h deposition. Effects of oxygen partial pressure on the structural, surface morphology, and photocatalytic activities of the TiO 2 thin films were investigated. We performed both photoinduced decompositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…From Fig. 1, it can be seen that all surfaces of TiO 2 films consist of the structure of the island [36]. For TiO 2 films with O 2 /Ar<6/14, the surface islands display the small size and large density.…”
Section: Resultsmentioning
confidence: 99%
“…From Fig. 1, it can be seen that all surfaces of TiO 2 films consist of the structure of the island [36]. For TiO 2 films with O 2 /Ar<6/14, the surface islands display the small size and large density.…”
Section: Resultsmentioning
confidence: 99%
“…Many materials have been used as substrates in magnetron sputtering, including organic materials (cotton fabrics [31] and polycarbonate [18,32]), inorganic materials (glass [16,33,34] and The gas pressure inside the chamber should not be very low in order to allow a collision between electrons and some atoms before the electrons hit the anode. If the gas pressure is very high, the electrons will neither reach enough velocity nor achieve enough energy in order to form new ions or excited species in the collisions.…”
Section: Substrate Typementioning
confidence: 99%
“…Many materials have been used as substrates in magnetron sputtering, including organic materials (cotton fabrics [31] and polycarbonate [18,32]), inorganic materials (glass [16,33,34] and quartz [35,36]), metals (wafers of alumina (Al 2 O 3 ) [37] zinc oxide (ZnO) [38], and stainless steel [39]), and minerals (sapphire [5]). Since the transmittance of PTFs affects the photocatalytic efficiency, materials such as glass and quartz are widely used as substrates due to their high transmittance.…”
Section: Substrate Typementioning
confidence: 99%
See 1 more Smart Citation
“…Dense coating provides very low permeability for electrolytes to establish an ionic conduct. The decrease in current density can be ascribed to the compact surface structure [32] and improved adhesion after decrease in oxygen partial pressure; at a lower oxygen flow rate, the nature of the substrate and oxygen flow can be an important factor influencing the quality of the coating [33], thereby reducing solution penetration and consequent localized corrosion. According to the corrosion surface, it was concluded that, after immersion for a period, the failure of the coatings could be ascribed to the micropores in the surface of coatings [34].…”
Section: Electrochemical Polarization Analysesmentioning
confidence: 99%